2021
DOI: 10.1590/1413-812320212611.3.05152020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rheumatoid arthritis in South America: a systematic review and meta-analysis

Abstract: Rheumatoid arthritis (RA) is among the most prevalent chronic autoimmune and inflammatory diseases worldwide. The aim of this study was to establish a pooled estimate of the RA prevalence in South America by means of a meta-analysis of the available epidemiologic studies. Systematic searches in PubMed, Lilacs, SciELO, Scopus, and Web of Science databases (updated May 2019) were done followed by a systematic grey literature search to identify original research articles and reports, published after 2000, providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…O chá da casca do uxi-amarelo é utilizado como anti-inflamatório e popularmente, é indicada para artrite reumatoide que é uma doença autoimune e inflamatória crônica [66,67] . Alguns estudos exploram a atividade anti-inflamatória da E. uchi e inclusive, um de seus compostos ativos, a bergenina, foi reportada como um potencial anti-inflamatório, o que pode comprovar o uso popular do uxi para artrite [13] .…”
Section: Atividade Anti-inflamatória Da Endopleura Uchiunclassified
“…O chá da casca do uxi-amarelo é utilizado como anti-inflamatório e popularmente, é indicada para artrite reumatoide que é uma doença autoimune e inflamatória crônica [66,67] . Alguns estudos exploram a atividade anti-inflamatória da E. uchi e inclusive, um de seus compostos ativos, a bergenina, foi reportada como um potencial anti-inflamatório, o que pode comprovar o uso popular do uxi para artrite [13] .…”
Section: Atividade Anti-inflamatória Da Endopleura Uchiunclassified
“…Microbial pathogenesis has been put forward as a cause of human autoimmune disorders; in particular, it has been suggested that attention should be paid to the potential pathogenic role of the obligate intracellular bacterial species Chlamydia pneumoniae ( C. pneumoniae ) [ 1 , 2 ]. The most prevalent chronic human autoimmune disorder worldwide is rheumatoid arthritis [ 3 ], and it is noteworthy that Fujita et al found a 30% prevalence of C. pneumoniae immunoglobulin M (IgM) in 27 patients in the acute phase of this illness (compared with a prevalence of 10% in controls) [ 1 ]. Furthermore, Gérard et al reported that synovial samples from all seven patients in their cohort of subjects with either rheumatoid arthritis or undifferentiated oligoarthritis proved polymerase chain reaction (PCR)-positive for C. pneumoniae DNA, while samples from a cohort of two patients with osteoarthritis were PCR-negative; moreover, reverse transcription (RT)-PCR assays targeting C. pneumoniae rRNA operons and mRNAs demonstrated that these synovial bacteria were metabolically active [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of patients with RA remains higher than that of the general population [ 5 , 6 ]. RA affects patients' quality of life and poses a significant social and economic burden on individuals, their families, and the community [ 7 ]. The underlying mechanism of RA is not yet fully clarified, therefore, it is important to have an intensive study on the nosogenesis of RA for targeted therapy of RA.…”
Section: Introductionmentioning
confidence: 99%